An Analysis of The Ability of Writing Narrative Text of The Tenth Grade Students of SMA Dharma Ayu Kefamenanu - Merlin Helentina Napitupulu; Yosefa Yemayo Ngao; Anselmus Sahan (CV. Eureka Murakabi Abadi, 2025)
This study focuses on examining the writing skills of tenth-grade learners at SMA Dharma Ayu Kefamenanu in crafting narrative texts during the academic year 2023/2024. Utilizing a descriptive qualitative approach, the research involved a sample of 30 students chosen through purposive sampling methods. Data were gathered from students' written narrative texts, which were subsequently assessed based on five key components of writing: content, organization, vocabulary, language usage, and mechanics. The results indicated that the students’ overall writing proficiency was categorized as